THE TRAINING AND COMPETENCE EFFECT OF PT BATIK TRUSMI CIREBON'S EMPLOYEE PERFORMANCE - Hidayat, Agi Syarif; Alwi, Muhammad; Setiawan, Yana (Jurnal Aplikasi Manajemen, 2017)
This study aims to determine the training and competence effect of PT. Batik Trusmi Cirebon's employee performance; the research used quantitative research method. The total of 69 employees of PT. Batik Cirebon was used as population samples in this study, frequency distribution and multiple regression are used as statistical analysis. Based on the hypothesis test results, it is known that F_calculate > F_ (table) is 93.879> 2.17, so it can be concluded that there is a positive and significant influence between the training and competence to the employee performance. Based on the result of the correlation coefficient is known that the value of R is 0.860, which implies a very strong degree of closeness between training and performance competence. Based on the coefficient of determination known that the value of Adjusted R Square is 0.732, which means equal to 73.2% of training and competence affect on employee performance and the rest of 26.7% influenced by the other factors that are not examined in this study.